Adsorption of CO2, CH4 and H2 onto zeolite 13 X: Kinetic and equilibrium studies - Hedi Jedli; Souhail Mohammed Bouzgarrou; Rym Hassani; Ehab Sabi; Khalifa Slimi (Heliyon)
Adsorption equilibrium and kinetics of CO2, H2 and CH4 on zeolite 13 X were carried out using the volumetric method. The zeolite 13 X was characterized via XRD, SEM and N2 adsorption-desorption. Adsorption isotherms of various gas were investigated over a full range of temperatures at 298, 308 and 313 K. Langmuir's equilibrium model and the heat of adsorption was used to correlate the adsorption isotherms over a wide range of pressure. A classical micropore diffusion approach was applied to investigate the kinetic adsorption. At 298 K, the selectivity of CO2/H2 and CO2/CH4 of the zeolite 13 X was 16.52 and 62.61, respectively. However, zeolite 13 X is one of the most suitable adsorbents for CO2 and CH4 storage, since it has a very high adsorption capacity for both gases. The influence of gas pressure on diffusivity for various absorber-adsorbent systems has been examined. The adsorption experiments with gas mixtures such as H2, CO2 and CH4 on 13 X zeolite show that this adsorbent has potential application in the gas separation and purification process.